A support system for the diagnosis of balance pathologies - Villa Monte, Augusto
Electronystagmography is one of the most widely used di- agnostic studies for detecting balance dysfunction. There are various methods that can be used to carry out this diagnostic test, gyratory stimulation being the least invasive and most physiological for the pa- tient. The procedure is based on measuring (analyzing) eye movements in search of certain patterns called nystagmuses. In this article, we introduce a hardware and software system for carrying out this type of studies that allows the healthcare professional to acquire, view, store, and manage results. The system also provides an intelligent method based on neural networks that can detect nystagmus patterns to help healthcare professionals make a diagnosis. The system is currently being used at a medical oce for the detection of balance disorders. Even though there are similar systems that are commercially available, these are usually very expensive due to their hardware equipment require- ments and use of proprietary technology. The system presented here was developed nationally at a very low cost and can be easily adapted to future changes in technology.